Serum Macrophage Colony-Stimulating Factor Relates to the Severity and the Pregnancy Outcomes in Hypertensive Disorders Complicating Pregnancy - Zhou, Lili; Liu, Junbo; Zhou, Min; Xu, Lan (Medical principles and practice, 2024)
Abstract Purpose: This study aimed to assess the predictive value of macrophage colony-stimulating factor (M-CSF) in the first trimester for hypertensive disorders complicating pregnancy (HDCP) and its association with disease severity and adverse pregnancy outcomes. HDCP pose significant risks to both maternal health and fetal health. M-CSF is implicated in the pathogenesis of HDCP by promoting inflammation and endothelial damage. Methods: Serum levels of M-CSF were measured using an enzyme-linked immunosorbent assay, and clinical characteristics and pregnancy outcomes were compared between groups. Results: Pregnant women with HDCP had significantly higher levels of proteinuria, systolic blood pressure, and diastolic blood pressure compared to those with normal pregnancy. Among patients with HDCP, the severity of disease correlated positively with serum levels of M-CSF. Furthermore, M-CSF levels in the first trimester were significantly associated with adverse pregnancy outcomes. The findings suggest that M-CSF may serve as a potential biomarker for predicting HDCP and its severity, as well as adverse pregnancy outcomes. Conclusions: Early detection and monitoring of M-CSF levels could aid in identifying high-risk pregnancies and implementing appropriate interventions to improve maternal and fetal outcomes.